2011
DOI: 10.1002/ajmg.a.34013
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of carpal tunnel syndrome in children with mucopolysaccharidosis type II (Hunter syndrome)

Abstract: Although carpal tunnel syndrome (CTS) is the most common compressive neuropathy seen in the upper extremity of adults, it is rarely seen in children. Several reports have shown that mucopolysaccharidosis type II (Hunter syndrome), a rare genetic disorder, is one of the causes of CTS in children. Usual symptoms of CTS are pain, weakness, and paresthesias in the hand and digits. However, the diagnosis of CTS in Hunter syndrome is often delayed or unrecognized because of atypical symptoms and cognitive impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 21 publications
0
28
0
2
Order By: Relevance
“…One of the problems in MPS is the high prevalence of carpal tunnel syndrome (CTS) in MPS subtypes I, II, and VI, [1][2][3][4] which -if not treated -often results in disabling, severe damage of the median nerve. Most MPS patients, however, do not report typical symptoms of CTS.…”
Section: Mpsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the problems in MPS is the high prevalence of carpal tunnel syndrome (CTS) in MPS subtypes I, II, and VI, [1][2][3][4] which -if not treated -often results in disabling, severe damage of the median nerve. Most MPS patients, however, do not report typical symptoms of CTS.…”
Section: Mpsmentioning
confidence: 99%
“…In 20 hands the changes were classified as moderate (1) and in 16 as prominent (2). The mean distal CSA was 14.0mm 2 (SD 12.2mm 2 , range 3-48mm 2 ).…”
Section: Mps Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have already been published about the CTS in MPS II revealed a frequency of the syndrome as high as 96 % [9].…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that have been made reveal a high frequency of the CTS in patients with MPS [8,9]. The diagnosis is usually established based on the clinical exam or nerve conduction studies.…”
Section: Introductionmentioning
confidence: 99%